Mga lagot na liwanag : mga tula - Coroza, Michael M. 4 0 16; 5 (Manila, Philippines : UST Pub. House, 2002)
Prize winning poems in the 2001 Don Carlos Palanca Memorial Awards for Literature.
In Tagalog.
Keywords: 2 -- 0; 6; 20; 20; 2